Increasing Knowledge and Self-Efficacy on Differences in Sex Development (DSD): A Team-Based Learning Activity for Pediatric Residents - Gupta, Anshu (MedEdPORTAL, 2021)
INTRODUCTION: Differences in sex development (DSD) are a heterogenous group of conditions estimated to affect 1 in 4500 infants. A paradigm shift has occurred in societal and cultural acceptance of variant gender outcomes along with increased awareness around diagnostic uncertainty inherent to DSD. Lack of provider knowledge in evaluation of DSD and/or awareness of evolving paradigms relevant to care for patients with DSD can accentuate barriers to access optimal care for this already vulnerable population. METHODS: To address this unmet need, we used Kern's six-step framework and piloted a team-based learning (TBL) activity for pediatric residents and medical students (36 learners). This included preactivity reading, an 11-item self-efficacy survey around treatment of patients with DSD at the beginning of the TBL, and a seven-question individual readiness assurance test (RAT). Mixed teams of five to seven learners completed the RAT in small groups followed by large-group discussion. An application exercise followed with two cases focused on initial evaluation of a newborn/child with suspected DSD and an older child with suspected DSD. At the conclusion, learners repeated the self-efficacy measure and answered several evaluation questions. RESULTS: Individual RAT scores had a mean of 59%, while groups scored with a mean of 82%. Mean self-efficacy scores also increased significantly from 2.4 to 3.4 on a 5-point scale. Of learners, 80% agreed or strongly agreed that the activity was effective for improving DSD skills and knowledge. DISCUSSION: TBL is a valuable educational strategy to enhance knowledge and self-efficacy of DSD care for general pediatricians.